2021
DOI: 10.1007/s00405-021-06983-3
|View full text |Cite
|
Sign up to set email alerts
|

T1 glottic laryngeal cancer: the role of routine follow-up visits in detecting local recurrence

Abstract: Purpose We assessed the treatment outcome and the benefits of routine follow-up visits in T1 glottic laryngeal squamous cell carcinoma (LSCC). Methods Medical records of patients diagnosed with stage T1 glottic LSCC (N = 303) in five Finnish university hospitals between 2003 and 2015 were reviewed. Moreover, data from the Finnish Cancer Registry and the Population Register Center were collected. Results Of all 38 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The 5-year overall survival of early-stage laryngeal carcinoma reported in the literature is high: 88% to 94%, 19,24,31 and the reported 5-year disease-specific survival is even better 97% to 99%. 19,28,32 Although the survival is favorable, the recurrence rate is considerable: percentages between 10% and 31% are reported, 19,24,27,[33][34][35][36][37] which is consistent with the recurrence rate of 23% we found. The recurrence rate is largely dependent on the follow-up duration that was maintained in different studies, for instance, the recurrence rate of 31% was found in a cohort with a follow-up duration of 15 years.…”
Section: Recurrencessupporting
confidence: 89%
“…The 5-year overall survival of early-stage laryngeal carcinoma reported in the literature is high: 88% to 94%, 19,24,31 and the reported 5-year disease-specific survival is even better 97% to 99%. 19,28,32 Although the survival is favorable, the recurrence rate is considerable: percentages between 10% and 31% are reported, 19,24,27,[33][34][35][36][37] which is consistent with the recurrence rate of 23% we found. The recurrence rate is largely dependent on the follow-up duration that was maintained in different studies, for instance, the recurrence rate of 31% was found in a cohort with a follow-up duration of 15 years.…”
Section: Recurrencessupporting
confidence: 89%
“…LSCC is characterized by local recurrence that seriously restricts LSCC therapy [ 20 , 21 ]. Thus, expanding our understanding of LSCC mechanisms provides effective targets for LSCC clinical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The potential prognostic value of mentioned hematological parameters regarding recurrence or progression of laryngeal dysplasia requires prospective, multicenter, randomized controlled studies to comprehensively evaluate the findings. The follow-up duration of 12 months seems to be quite short for the recurrence or cancerization observation; however the majority of the T1 glottic cancer relapses appear within first 24 months and are asymptomatic ( Pakkanen et al, 2021 ) Moreover, the late relapses are more dependent on continued exposure to risk factors. The early ones are more dependent on internal biological mechanisms.…”
Section: Discussionmentioning
confidence: 99%